Permeability function of unsaturated soil with multi-modal porosity - Chong, Jie Sheng (Nanyang Technological University, 2022)
In unsaturated soil mechanics, hydraulic properties such as soil-water characteristic curve (SWCC) and unsaturated permeability function are the fundamental parameters governing most of the engineering properties of soil. Ensuring slope stability during intensive rainfall and vegetation survival in prolonged drought are the main reasons for studying hydraulic properties. By determining the soil’s SWCC and unsaturated permeability function, rainfall-induced slope failure and wilting point of plants can be avoided as matric suctions and water flux along soil depth can be predicted accurately. Multimodal porosity soil was proven to have multimodal characteristics in SWCC, which exhibit higher water retention capabilities that favour the vegetation growth. In addition, the multimodal SWCC characteristics of soil can be further enhanced by introducing porous materials like activated carbon. The main objective of this study is to investigate the permeability function of unsaturated soil with multimodal porosity. In this research, two bimodal soils of sand-kaolin mixtures were prepared for laboratory tests, namely SKP with the addition of powdered activated carbon and SKG with the addition of granular activated carbon. Dynamic compaction, standard compaction, index properties test, drying SWCC test, shrinkage test, saturated permeability test and unsaturated permeability test were conducted. The drying SWCC tests were done by three methods, 1) the conventional method by using Tempe cell and pressure plate, 2) Schindler (1980)’s method by using HYPROP device and 3) the newly proposed Osmotic Tensiometer (OT) permeameter. The direct measurement of unsaturated permeability using Schindler (1980)’s method was then compared with the permeability functions estimated from the modified Satyanaga et al.’s best-fitting equation for trimodal SWCC. The experimental results showed that SKP and SKG mixtures exhibited trimodal drying SWCC from all the measurements, but the Schindler’s evaporation method displayed a subtle trimodal SWCC with a higher water retention capability. The comparison between the direct measurement of unsaturated permeability with the estimated permeability function showed a justifiable agreement by having similar trimodal curves within a tolerable range of coefficient of permeability (k). The results proved that Schindler’s method by using OT permeameter is a practical way of determining unsaturated permeability of multimodal soil, based on the premise of permeability function estimated from the Kunze et al.’s (1968) statistical equation.